MONITORING NILAI PH, SUHU, DAN KEKERUHAN AIR PADA PDAM DI KECAMATAN BELINYU BERBASIS IOT - Putri Alwiyah; Stieven Elizer; Eko Sulistyo; Indra Dwisaputra; Charlotha Charlotha (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
PDAM Belinyu currently has water quality that has not yet reached the standard. Therefore, a measuring instrument is needed to monitor the pH value, temperature, and water turbidity. This study aims to make it easier for PDAM employees to check the IoT-based pH, temperature, and turbidity values of water. The method used in this research is data collection, block diagram design, testing, and data analysis. Based on the tests that have been carried out, the percentage error on the pH sensor sample 1 is 0.000457671% and sample 2 is 0.068227799%, the percentage error on the temperature sensor is 0.7699637% and the average data on the clean water turbidity sensor is 0, 6 NTU and cloudy water of 25.8 NTU.